Airway Epithelial Cell-Derived Colony Stimulating Factor-1 Promotes Allergen Sensitization - Moon, Hyung-Geun (Immunity, 2018)
Airway epithelial cells (AECs) secrete innate immune cytokines that regulate adaptive immune effector cells. In allergen sensitized humans and mice, the airway and alveolar microenvironment is enriched with colony stimulating factor-1 (CSF1) in response to allergen exposure. In this study we found that AEC-derived CSF1 had a critical role in the production of allergen reactive-IgE production. Furthermore, spatiotemporally secreted-CSF1 regulated the recruitment of alveolar dendritic cells (DCs) and enhanced the migration of conventional DC2 (cDC2) to the draining lymph node in an interferon regulatory factor 4 (IRF4) dependent manner. CSF1 selectively upregulated the expression of the chemokine receptor CCR7 on the CSF1R(+)cDC2, but not the cDC1, population in response to allergen stimuli. Our data describe the functional specification of CSF1-dependent DC subsets that link the innate and adaptive immune responses in T helper-2 (Th2) cell-mediated allergic lung inflammation.